AKUPRESUR DENGAN PELVIC ROCKING KOMBINASI AROMATHERAPY LAVENDER MENGURANGI DISMINORE SISWA MTS NU 05 SUNAN KATONG - Rose Nur Hudhariani; Gurnita, Fauziah Winda; Maftuchah, Maftuchah; Wahyunik, Siti Ida (Jurnal Kebidanan, 2024)
Background: According to WHO 2020 (World Health Organization) , 90% of Indonesian women suffer from dysmenorrhea. Primary dysmenorrhea 72.89%, secondary dysmenorrhea 21.11%, of which 1.31% patients with dysmenorrhea go to midwives.. Results of interviewing 5 people, in which 4 people have dysmenorrhea and only 1 person din’t have dysmenorrhea. Objective: To determine the effectiveness of combining Li4 acupressure with lavender aromatherapy toward the level dysmenorrhea in Mts Nu 05 Sunan Katong Kaliwungu Research Methods: The type of reserch used quasy experimental with the design of two group pre test post test with the intervention of giving Li4 acupressure with lavender aromatherapy and pelvic rocking exercises with lavender aromatherapy. The population is all students of Mts Nu 05 Sunan Katong Kaliwungu and the total sample is 32 students according to inclusion and exclusion criteria. The sampling technique used is accidental sampling. Result: There was a significant effect on Li4 acupressure with lavender aromatherapy and pelvic rocking exercises with lavender aromatherapy on the level of dysmenorrhea pain in Mts Nu 05 Sunan Katong Kaliwungu. The results showed that there was no significant difference between Li4 acupressure with lavender aromatherapy and pelvic rocking exercises with lavender aromatherapy. Conclusion: There is a relationship between Accupresure Li4 with lavnder aromatherapy and Pelvic rocking exercises with lavender aromatherapy at Mts Nu 05 Sunan Katong Kaliwungu. Keywords: Li4 accupressure, Lavender aromatherapy, Dysmenorrhoea, Pain Levels, Pelvic rocking Exercise,